PARKOUR AND RECREATIONAL ACTIVITIES - Ciekurs, Kalvis; Zangerl, Rudi; Kravalis, Ivars; Vazne, Žermēna; Kaupužs, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Recreation philosophy is human ability to relax applying various games and activities, where a game or activity has some purpose, which we should know and understand how to achieve it. Parkour is a movement, form of training, a way of getting it, the art of moving from point A to point B with your own body as a means in as fast, efficient and controlled manner as possible based on your own circumstances. It is completely free from competitions, competitions or other forms of rivalry. Recreation is for people to restore from everyday work routine and stress. Practically people perceive this essence of recreation which gives us a possibility to relax and creates emotions of happiness. Parkour is an art that helps you pass any obstacle to go from point A to point B using only the abilities of the human body. One of recreation and parkour kinds is outdoor activities, which means different open-air activities in nature. Outdoor activities have a physical, mental, emotional and even educational effect on a participant. Recreation and parkour activities are not organized like competitions, to participate in them there are no rules made. People who go in for recreation outdoors need only space on the land, water or in the air. It is an activity which allows an individual to renew interacting with the nature in cities and villages, as well as in virgin nature territories. What separates them from parkour is that they contain more acrobatic and spectacular movements and where there may be an assessment in the performance. Recreational activities and parkour activities have many symbioses, sometimes we can Sayed recreational parkour (parkour of basics) for everyone. We are getting great emotions and physical well-being.